Chromium-Catalyzed Cross-Couplings and Related Reactions - Li, Jie; Knochel, Paul (Synthesis, 2019)
Transition-metal-catalyzed cross-couplings have been recognized as a powerful tool for sustainable syntheses. Despite the fact that remarkable progress was achieved by palladium and nickel catalysis, the high price and toxicity still remained a drawback. Recently, naturally more abundant and less toxic low-valent chromium salts, such as Cr(II) and Cr(III) chlorides, displayed notable unique catalytic reactivity. Thus, recent progress in the field of chromium-catalyzed cross-couplings and related reactions are highlighted in the present short review until December 2018.1 Introduction and Early Chromium-Mediated Reactions2 Chromium-Catalyzed Cross-Couplings and Related Reactions3 Conclusion
Keywords: chromium; cross-coupling; C–H activation; C–X formation; homogeneous catalysis